Cover Image. (9th December 2021) - Fordham, Damien A.; Brown, Stuart C.; Akçakaya, H. Reşit; Brook, Barry W.; Haythorne, Sean; Manica, Andrea; Shoemaker, Kevin T.; Austin, Jeremy J.; Blonder, Benjamin; Pilowsky, Julia; Rahbek, Carsten; Nogues‐Bravo, David
Abstract : The cover image is based on the Letter Process‐explicit models reveal pathway to extinction for woolly mammoth using pattern‐oriented validation by Damien A. Fordham et al., https://doi.org/10.1111/ele.13911 . Image Credit: Mauricio Anton.